TNF-alpha in asthma. - Berry, M; Brightling, C; Pavord, I; Wardlaw, A (2007)
Although only 5-10% of patients with asthma are relatively unresponsive to treatment with inhaled corticosteroids, refractory asthma represents an important condition, as these patients suffer considerable morbidity and mortality and consume a disproportionately large amount of health resource. Treatment options are limited and there is a large unmet clinical need for additional therapies. Tumour necrosis factor (TNF)-alpha is a pro-inflammatory cytokine that has been implicated in many aspects of the airway pathology in asthma, and which has recently been highlighted as potentially important in refractory asthma. The development of neutralising biological agents against TNF-alpha has allowed us to test the role of this cytokine in vivo. Preliminary studies have demonstrated an improvement in lung function, airway hyperresponsiveness and asthma quality-of-life, together with a reduction in exacerbation frequency, in patients treated with anti-TNF-alpha therapy.